2023
DOI: 10.1093/nargab/lqad062
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of a semicontinuous trait: illustration of the impact of the modeling strategy through the study of Neutrophil Extracellular Traps levels

Abstract: Over the last years, there has been a considerable expansion of genome-wide association studies (GWAS) for discovering biological pathways underlying pathological conditions or disease biomarkers. These GWAS are often limited to binary or quantitative traits analyzed through linear or logistic models, respectively. In some situations, the distribution of the outcome may require more complex modeling, such as when the outcome exhibits a semicontinuous distribution characterized by an excess of zero values follo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…A description of the study can be found in, 28 and the genotyping procedures and quality controls are available in. 30 …”
Section: Methodsmentioning
confidence: 99%
“…A description of the study can be found in, 28 and the genotyping procedures and quality controls are available in. 30 …”
Section: Methodsmentioning
confidence: 99%